2020
DOI: 10.3389/fneur.2020.607766
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Lymphoid Follicles in Multiple Sclerosis: Centers for Disease Control?

Abstract: While the contribution of autoreactive CD4+ T cells to the pathogenesis of Multiple Sclerosis (MS) is widely accepted, the advent of B cell-depleting monoclonal antibody (mAb) therapies has shed new light on the complex cellular mechanisms underlying MS pathogenesis. Evidence supports the involvement of B cells in both antibody-dependent and -independent capacities. T cell-dependent B cell responses originate and take shape in germinal centers (GCs), specialized microenvironments that regulate B cell activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 208 publications
(301 reference statements)
0
21
0
3
Order By: Relevance
“…Inside the brain, the TLO found in the meninges are the driving force of the autoimmune pathogenic process. 91 It has been proposed that previous EBV infection, vitamin D deficiency, and/or a genetic substrate may be the initiators or determinants of the disease process in MS. The B cell lineage plays a crucial role in the pathogenesis of MS and remains active during the course of the disease, in the periphery and CNS, and an aggressive depletion with current therapies can only control the clinical activity and slow down the progression toward disability.…”
Section: Discussionmentioning
confidence: 99%
“…Inside the brain, the TLO found in the meninges are the driving force of the autoimmune pathogenic process. 91 It has been proposed that previous EBV infection, vitamin D deficiency, and/or a genetic substrate may be the initiators or determinants of the disease process in MS. The B cell lineage plays a crucial role in the pathogenesis of MS and remains active during the course of the disease, in the periphery and CNS, and an aggressive depletion with current therapies can only control the clinical activity and slow down the progression toward disability.…”
Section: Discussionmentioning
confidence: 99%
“…A burgeoning area of research within MS is the study of CNS ELFs, which are aggregates of lymphoid cells within non-lymphoid tissues with varying degrees of similarity to germinal centers within secondary lymphoid organs. ELFs can be found in the CNS in MS ( 104 , 105 ) and its animal models ( 47 , 106 ). Some investigators ( 107 ), but not others ( 108 ), have found that meningeal ELFs are associated with cortical demyelination.…”
Section: Fiction #4 the Immune Response In Ms Is Dominated By Antigen...mentioning
confidence: 99%
“…It is believed that such B-cell structures are particularly likely to contribute to cortical demyelination and disease progression. Moreover, it has recently been found that meningeal B-cell follicles are formed from the earliest stages of demyelination, which may explain neurodegenerative changes at the disease onset [20,21].…”
Section: Mechanisms Of B Cell Involvement In the Immunopathogenesis Of Ms (Antibodies Cytokines Antigen Presentation)mentioning
confidence: 99%